Strategic Innovation in Waqf Management: A Case Study of Muhammadiyah Association in Palembang City (UIN Sunan Kudus, 2025)
This study aims to examine the strategies implemented by the Muhammadiyah Association of Palembang City to enhance the welfare benefits of waqf. This is a field study employing a qualitative approach. Data were collected through observation, in-depth interviews, and document analysis. The findings indicate that the waqf assets managed by Muhammadiyah in Palembang City primarily consist of land and buildings, which are generally utilized for educational, religious, health, and social facilities. Additionally, there is significant potential for cash waqf, estimated to reach approximately IDR 1.6 billion per year. To ensure that waqf management by Muhammadiyah Palembang City contributes effectively to public welfare, as stipulated in Law No. 42 of 2004 concerning waqf, several strategic shifts are necessary. First, a paradigm shift is required from a traditional to a contemporary waqf management model. Second, the professionalism of the nazir (waqf managers) must be enhanced. Third, innovative approaches to productive waqf programs should be pursued, including the management of neglected waqf assets, the development of existing assets, and the establishment of new waqf initiatives. Fourth, the management of cash waqf must be optimized. Fifth, waqf administration needs to be systematically structured.